Investigating the effect of academic procrastination on the frequency and variety of academic misconduct: a panel study - Patrzek, Justine (Studies in higher education, 2015)
In prior studies, academic procrastination has been discussed as an influencing factor of academic misconduct. However, empirical studies were conducted solely cross-sectionally and investigated only a few forms of academic misconduct. This large scale web-based study examined the responses of between 1359 and 2207 participants from different academic disciplines at four German universities to address the effect of academic procrastination on seven different forms of academic misconduct (using fraudulent excuses, plagiarism, copying from someone else in exams, using forbidden means in exams, carrying forbidden means into exams, copying parts of homework from others, and fabrication or falsification of data) and its variety. In measuring academic procrastination six months prior to academic misconduct, we found that academic procrastination affected the frequency of all forms of academic misconduct and its variety. We found the strongest effect of academic procrastination on using fraudulent excuses. Implications for university counseling and theory are discussed.